2016
DOI: 10.1097/ede.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heart Transplant Waitlist Time and Pre- and Post-transplant Failure

Abstract: Background Over the past two decades there have been increasingly long waiting times for heart transplantation. We studied the relationship between heart transplant waiting time and transplant failure (removal from the waitlist, pre-transplant death, or death or graft failure within one-year) to determine the risk that conservative donor heart acceptance practices confer in terms of increasing the risk of failure among patients awaiting transplantation. Methods We studied a cohort of 28,283 adults registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…To date, a number of consensus statements (4,5) and risk models (6,7) have been published in an attempt to codify knowledge around donor heart selection. What we know is that more patients are waiting for heart transplantation every year, that there is a positive association between time spent on the waitlist and mortality (8) and that the criteria used for donor heart selection must be questioned, challenged, and expanded in order to meet the evergrowing demand for heart transplantation. This Perspective discusses recent advances in the field that should help guide and expand use of available donor hearts in the modern era.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of consensus statements (4,5) and risk models (6,7) have been published in an attempt to codify knowledge around donor heart selection. What we know is that more patients are waiting for heart transplantation every year, that there is a positive association between time spent on the waitlist and mortality (8) and that the criteria used for donor heart selection must be questioned, challenged, and expanded in order to meet the evergrowing demand for heart transplantation. This Perspective discusses recent advances in the field that should help guide and expand use of available donor hearts in the modern era.…”
Section: Introductionmentioning
confidence: 99%
“…Even nowadays it can be lifesaving for patient that is not a candidate for an MCS, such as those with hypertrophic cardiomyopathy or some complex forms of congenital heart disease and those needing a re-transplantation. As has been shown in several countries dealing with growing waitlists, a prolonged waiting time negatively impacts post-transplant survival (11). Many patients that were good candidates at the moment of listing, may turn out poor recipients 2 years later.…”
Section: Discussionmentioning
confidence: 99%
“…This has not only resulted in scientific output, but has also likely lowered the threshold for patients to contact the transplant nurses and physicians in case of questions or problems. It may have also assisted in creating a culture where patients and their families form a team together with Primary graft failure [16] Acute rejection [7] Late graft failure (HFrEF) [6] [Non] STEMI [4] Post-PCI/CABG [3] Technical problems during HTx [3] Stroke/intracranial bleeding [12] Aortic rupture [4] Intestinal ischemia [3] Malignancy 78 [32] Lung [35] GI tract [10] PTLD [9] Kidney-bladder [6] Pancreas [4] Blood [4] Prostate [3] Skin [3] Primary tumor unknown [3] Brain [1] Infection 43 [18] Pneumonia [22] Sepsis [15] Other [6] Other 27 [11] Old age [8] Dementia [5] Suicide [4] Therapy withdrawal [3] Trauma [3] Respiratory failure [1] Bleeding [1] ALS [1] Euthanasia [1] Finally, we pay a lot of attention to cardiovascular prevention and screening for malignancies. The significant and consistent decreases in age-adjusted cardiovascular mortality shown in European and US registries was attributed to better prevention and better treatment of cardiac disease (29).…”
Section: Discussionmentioning
confidence: 99%
“…• Reducing the HTx referrals to 1% (transplant rates) every month, as donor hearts are expected to become scarce. 21 • Improved survival to reflect improved LVAD performance, as recent studies showed that long-term performance of LVAD had improved in the recent era. 22,23 • Higher costs for the management of 'no LVAD' group because of prolonged intensive care unit (ICU) stay (mean ICU costs €42 000/month).…”
Section: Economic Evaluation Of Lvad In Francementioning
confidence: 99%